2017
DOI: 10.1038/s41598-017-00205-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term magnesium supplementation on endothelial function and cardiometabolic risk markers: A randomized controlled trial in overweight/obese adults

Abstract: Long-term magnesium supplementation improves arterial stiffness, a cardiovascular disease risk marker. Effects on endothelial function may be another mechanism whereby increased magnesium intakes affect cardiovascular risk. Therefore, a 24-week, randomized, double-blind, placebo-controlled trial was performed to examine effects of magnesium supplementation on endothelial function and cardiometabolic risk markers. Fifty-two overweight and obese subjects (30 men and 22 women, age 62 ± 6 years) were randomized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 43 publications
(63 reference statements)
5
32
1
1
Order By: Relevance
“…Magnesium could potentially confer protection against CAD by enhancing endothelium-dependent vasodilation and reducing vascular resistance, oxidative stress and oxidised lipids, inflammation and thrombosis, and by anti-arrhythmic effects [ 2 , 4 , 7 , 16 , 17 ]. Several [ 8 , 9 , 13 ] but not all [ 38 , 39 ] randomised trials have shown that magnesium supplementation improves endothelial function and reduces arterial stiffness. The inconsistent results may be related to magnesium status among study participants, as improvement in endothelial function with magnesium supplementation was observed in trials involving patients with low serum magnesium levels [ 9 ] and patients using diuretics [ 8 ], which often cause hypomagnesaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium could potentially confer protection against CAD by enhancing endothelium-dependent vasodilation and reducing vascular resistance, oxidative stress and oxidised lipids, inflammation and thrombosis, and by anti-arrhythmic effects [ 2 , 4 , 7 , 16 , 17 ]. Several [ 8 , 9 , 13 ] but not all [ 38 , 39 ] randomised trials have shown that magnesium supplementation improves endothelial function and reduces arterial stiffness. The inconsistent results may be related to magnesium status among study participants, as improvement in endothelial function with magnesium supplementation was observed in trials involving patients with low serum magnesium levels [ 9 ] and patients using diuretics [ 8 ], which often cause hypomagnesaemia.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study that also found magnesium supplementation did not significantly affect markers of chronic low-grade inflammation can be critiqued in a similar manner. 39 Magnesium was supplemented for 24 weeks in 52 overweight/obese individuals with mean serum magnesium concentrations ranging from 0.84 to 0.87 mmol/L. In these apparently magnesium-adequate individual, magnesium supplementation did not decrease adhesion factors serum VCAM-1, ICAM-1, and E-selectin.…”
Section: Introductionmentioning
confidence: 95%
“…In these apparently magnesium-adequate individual, magnesium supplementation did not decrease adhesion factors serum VCAM-1, ICAM-1, and E-selectin. 39 A recent systematic review and meta-analysis of randomized controlled trials support the suggestion that magnesium supplementation will affect markers of inflammatory stress only when they are elevated. 40 In the overall meta-analysis, magnesium treatment did not significantly affect CRP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a study examined the effects of Mg 2+ supplementation on the endothelial function of overweight and obese individuals, middle-aged adults, and the elderly, subjected to a daily magnesium supplement of 350 mg for 24 weeks. There was no observed improvement in soluble vascular cell adhesion molecule (sVCAM)-1, soluble intercellular adhesion molecule (sICAM)-1, and soluble endothelial selectin (sE-selectin), along with no change in FMD markers of endothelial function or inflammatory parameters [ 41 ].…”
Section: The Role Of Mg 2+ In Hematopoiesismentioning
confidence: 99%